PENERAPAN MANAJEMEN PEMASARAN PT. RITA RITELINDO PURWOKERTO DALAM MENGHADAPI PERKEMBANGAN EKONOMI GLOBAL - Wijayanto, Pikir Wisnu (Pro Bisnis, 2010)
The purposes of this research are to know the implementation of marketingstrategies at Rita Ritelindo Iurwokerto Company and thi anticipation offacing thbeconomic global development. The research method used was the interview andobsemation, The research conducted tn some business unit in order to lrnow the realcondrtion and implementation progress in each unit. Based on the researchs resultand data analysis, it can be concluded that Rita Ritelindo Purwokerto Company hasdone some marketing stategies in facing the development of economic global such asbeing pro active to the customers, analyse the market condition, make the best ofroles and resources function properties, arrange oriented sftategies, in everybusiness units, and do promotion elfectively